Peran Manajemen Perubahan dalam Menghadapi Tantangan dan Mengoptimalkan Peluang di Era Digital (2023-07-03) - Muspiroh Muspiroh; Faisal Dudayef; Cecinia Hayati Siburian; Putri Amaliah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Digital transformation has become imperative for organizations worldwide, yet the failure rate of these initiatives remains significantly high. This article aims to analyze the strategic role of Change Management in bridging the gap between technology adoption and human resource readiness. Using a descriptive qualitative method and recent literature review (2019-2023), this study finds that the main challenge in the digital era lies not in technological complexity, but in cultural resistance and employee mental unpreparedness. The results indicate that change management approaches focused on human-centric design, transparent communication, and digital upskilling are key to turning digital disruption into sustainable competitive opportunities. Effective digital transformation requires a deep understanding of organizational dynamics and employee attitudes toward change. Proper application of change management principles can reduce resistance, enhance collaboration, and ensure smoother technology adoption. Therefore, it's crucial for companies to integrate ongoing training and support into every stage of the digital transition to maximize its potential.